2004
DOI: 10.2460/javma.2004.224.879
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic study of relationships between consumption of commercial canned food and risk of hyperthyroidism in cats

Abstract: These findings suggest that the increasing prevalence of feline hyperthyroidism is not solely the result of aging of the cat population and that canned foods may play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
133
5
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(162 citation statements)
references
References 37 publications
7
133
5
17
Order By: Relevance
“…However, 955 cats were excluded from this study owing to the exclusion criteria, and cats younger than 7-years-old were not examined. Thus, the real prevalence of hyperthyroidism in cats from Warsaw is likely to be rather lower, especially in younger cats, but in comparison with the results of previous research in other regions seems to be very high (2,5,10,17).…”
Section: Discussioncontrasting
confidence: 37%
See 3 more Smart Citations
“…However, 955 cats were excluded from this study owing to the exclusion criteria, and cats younger than 7-years-old were not examined. Thus, the real prevalence of hyperthyroidism in cats from Warsaw is likely to be rather lower, especially in younger cats, but in comparison with the results of previous research in other regions seems to be very high (2,5,10,17).…”
Section: Discussioncontrasting
confidence: 37%
“…Moreover, the occurrence of hyperthyroidism in cats has increased since 1979 (14). Edinboro et al (5) showed that age-adjusted prevalence increased from 0.1% to 2% in 1978-1997 in the United States. Mooney (11) pays attention to increased longevity in cats; with an increased risk of the occurrence of the disease in older cats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyperthyroidism in cats is a common endocrine disease of geriatric cats and is the result of autonomous secretion of thyroxine (T 4 ) and triiodothyronine (T 3 ) by the thyroid gland 1. Treatment options include administration of oral antithyroid drugs (methimazole or carbimazole), thyroidectomy, or administration of 131 iodine ( 131 I).…”
mentioning
confidence: 99%